Sequestration of Pb(II) from aqueous environment by palm kernel shell activated carbon: isotherm and kinetic analyses - Isokise, Ekemini Monday; Abdullah, Abdul Halim; Tan, Yen Ping (Universiti Putra Malaysia Press, 2021)
In this work, activated carbons were produced by the thermochemical treatment of palm kernel shells with different activation time. The developed products (activated carbon samples) were described by their surface area, porosity, and applied for lead(II) ions separation from liquid phase. By prolonging the activation time beyond 2h, some of the micropores collapsed to form mesopores without causing a significant transformation in the surface area. The influences of solution pH, mass of biosorbents, concentration of Pb(II) ions, and temperature on the entrapment of lead(II) ions explored. Based on experimental outcome, the best-suited condition for the Pb(II) uptake was 0.13 g AC-4, 250 mg L-1 concentration, and pH 4. The Pb(II) entrapment process is thermodynamically exothermic and spontaneous. The adsorption data fit the Langmuir monolayer adsorption model, with 222 mg g-1 as maximum sorption capacity, and the Ho-second-order kinetics model suitably described the process rate.